Smallholder farmers’ knowledge on management of Cinchona in the Democratic Republic of the Congo - Mekonnen, Bezawit; Cizungu, Landry; Alegre, Julio; Blondeel, Haben; De Lombaerde, Emiel; Verbeeck, Hans; Duchateau, Luc; Schrevens, Eddie; Verheyen, Kris; Boeckx, Pascal; De Frenne, Pieter (Plant ecology and evolution, 2025)
Background and aims – Cinchona (Rubiaceae) tree bark is the key source of quinine alkaloids used as malaria treatment. Cinchona trees were introduced to Democratic Republic of the Congo (DRC) in the early 20 th century. Currently, the eastern DRC accounts for an estimated 55% of the global supply of quinine. The aim of this study is to obtain more insights into what context Cinchona is cultivated, what the scale of the farming and its management is, and how specific risks are being dealt with. Material and methods – Data was collected on Cinchona tree distribution, socio-economic variables, farm characteristics, and cultivation techniques based on interviews with 185 smallholder farmers in five regions ( groupements ) across the eastern DRC. Key results – Most Cinchona trees are grown at elevations between 1588 and 1627 m a.s.l. and most farmers preferred growing C. calisaya in a monoculture cultivation system, with in vivo propagation, and their own seed sources. Cassava was the dominant crop as previous cultivation and as a crop grown together with Cinchona . Eucalyptus was the dominant tree species grown together with Cinchona . Furthermore, most of the farmers apply a 1 × 1 m spacing and most do not use any additional fertilizer input. The most reported plant disease is linear canker. Conclusion – To sustainably increase the productivity of Cinchona in the DRC, smallholder farmers should be given appropriate training to empower them to carry out their own in vitro propagation and apply integrated soil fertility management and integrated pest management. Our results provide information on current cultivation of Cinchona in the DRC, which may become more important given the rising resistance of the malaria parasite against other medicines.